Кримінально-правові засоби стримування рецидивної злочинності - Телефанко, Б.; Telefanko, B. (Східноєвропейський національний університет імені Лесі Українки, 2015)
Стаття присвячена складним питанням стримування рецидивної злочинності кримінально-правовими засобами. В Україні рецидивісти з кожним роком виступають все більш на перший план. Чим більша кількість попередніх покарань, тим сильніша стає небезпека нового рецидиву. Ефективність стримування рецидивної злочинності не залежить виключно від кримінально-правових засобів. Кримінальне покарання, його призначення і виконання є лише допоміжним засобом стримування цього негативного явища і його серцевини – рецидивної злочинності. Позитивних результатів у справі стримування рецидивної злочинності можна добитися, проводячи комплексні заходи, які охоплюють всі сфери життєдіяльності, а саме економіку, політику, право і культуру. The article is devoted to difficult questions of restraining of recurrent crime by means of criminal and legal measures. In Ukraine recidivists act more and more at the forefront every year. The bigger number of former punishments is, the stronger danger of new recurrence becomes. Essential criminal and legal means of controlling recurrence of crimes are the following: timely detection and solving of crimes, scrupulous study of the person in course of investigation, right and reasonable choice of the appropriate measure of restraint, imposing of fair punishment (its real serving), taking into account requirements for differentiation and individualization, steady ensuring of principles of inevitability and more severe penalty of criminals for a new crime. Also the attention is paid to the necessity of strict observance of the mode in places of restriction and imprisonment, active educational and pedagogical influence, encouragement for the slightest positive actions in places of restriction and imprisonment, help in the household and work arrangement. Fast identification and disclosure of crimes will provide awareness of inevitability of punishment and will constrain from commission of recurrent crimes. Punishment is aimed at neutralizing criminal behaviour, and if the delay of its execution is applied, the convicts consider it equivalent to the release from responsibility. There is a threat not to use more severe penalty, therefore the potential of institution of punishment is not used.
Criminal and Legal Means to Restrain Recurrent Crime
Keywords: рецидивна злочинність; покарання; кримінально-правові засоби; рецидив злочинів; рецидивіст; recurrent crime; punishment; criminal and legal measures; recurrence of crimes; recidivist